2007
DOI: 10.1140/epje/i2007-10213-5
|View full text |Cite
|
Sign up to set email alerts
|

Monomer dynamics in single- and double-stranded DNA coils

Abstract: In our paper (Tothova et al., Czech. J. Phys. 55, 221 (2005)), the first observation of the kinetics of individual polymer monomers using the fluorescence correlation technique (R. Shusterman et al., Phys. Rev. Lett. 92, 048303 (2004)) has been interpreted within the bead-spring theory. Optimizing the joint Rouse-Zimm model to the experimental data, the phenomenological parameters for the statistical-mechanical description of the universal behavior of double- and single-stranded DNA and the dominant types of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
0
16
1
Order By: Relevance
“…This seems to be a combined dynamics of Rouse-and Zimm-type which can be explained by the so called RouseÀZimm model. 10 But the results we get are rather di®erent with that of Tothova et al 10,11 while their calculation suggested a strong HI applicable to Zimm model. Up to now, we do not know why this would happen for a relatively weak HI which can be interpreted by neither model, perhaps partially owing to processes related to the internal dynamics of the°uorophore or the semi-°exible nature of dsDNA.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…This seems to be a combined dynamics of Rouse-and Zimm-type which can be explained by the so called RouseÀZimm model. 10 But the results we get are rather di®erent with that of Tothova et al 10,11 while their calculation suggested a strong HI applicable to Zimm model. Up to now, we do not know why this would happen for a relatively weak HI which can be interpreted by neither model, perhaps partially owing to processes related to the internal dynamics of the°uorophore or the semi-°exible nature of dsDNA.…”
Section: Discussioncontrasting
confidence: 79%
“…Up to now, we do not know why this would happen for a relatively weak HI which can be interpreted by neither model, perhaps partially owing to processes related to the internal dynamics of the°uorophore or the semi-°exible nature of dsDNA. 10 As for a new model beyond Rouse and Zimm 6 or nonlinear HI, 4,9 more experimental and theoretical work need to be done.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we shall briefly focus on the simplest (but observable [6]) motion of the end monomer within a polymer coil and calculate its mean square displacement (MSD). The MSD part due to internal modes is [4,11] …”
Section: Monomer Motionmentioning
confidence: 99%
“…In the literature, following de Gennes [10], it is assumed that at θ conditions, the Zimm modes with the dispersion of relaxation times τ pZ ∼ p −3/2 , where p is the mode number, at low frequencies, should always dominate the Rouse modes with τ pR ∼ p −2 ; we show that these both contributions to the polymer characteristics should be taken into account. Next, the internal modes are distributed discretely (the assumption of their continuous distribution with respect to p is true only in a restricted time domain and often leads to incorrect interpretation of experimental data [11]. The formalism from our theory with the time-dependent hydrodynamics of polymers has been adopted [9,12] and, finally, the Brinkman's theory [13,14] for the flow in porous media is used in order to take into account the effect of other coils on the test polymer.…”
Section: Introductionmentioning
confidence: 99%